Variação espaço-temporal da taxocenose de colêmbolos (Hexapoda: Collembola) em ambientes cavernícolas interligados pelo habitat subterrâneo superficial (HSS), no quadrilátero ferrífero (rocha ferruginosa), MG – Brasil - Brito, Roniere Andrade de (2020)
Caves are natural subterranean environments formed by a complex ecosystem, with animal species adapted to deep zones, characterized by the total absence of light, oligotrophy, temperature with low circannual oscillation and humidity at the limit of saturation. In Brazil, the changes in the legislation about cave, which now allows the suppression, has intensified studies in the Quadrilátero Ferrífero (QF) areas mineral, Minas Gerais, Brazil, due to economic value of high concentration iron caves. Springtails are known worldwide and used to monitor anthropogenic impacts on environment. The Collembola fauna can occupy the entire area of cave, from the shallow little of water to canals that communicate with the Shallow Subterranean Habitats (SSH), as defined by rock cracks, which allow species to communicate between caves and initial horizons of ground. To understand the spatial and temporal variation of springtails in the cave environment and communication with the SSH, collections were carried out in three areas distributed between Serra da Moeda (Serrinha and Capitão do Mato) and Serra do Gandarela (Apolo) in 2016 and 2017. Temperature and humidity variables were also analyzed and correlated with biotic data. The results indicate that the richness is influenced by temperature, and has no significant difference inside or outside the cave. While abundance is influenced by humidity and differs between the hypogean and epigean environments. The composition of springtails varies inversely between dry periods – higher richness and lower abundance, and rainy season – higher abundance and lower richness, regardless of the environment. The exception is the aphotic zone which has greater richness and abundance in dry season. The most common genus recorded was Pseudosinella Schäffer, 1897 followed by Cyphoderus Nicolet, 1842. SSH has humidity as the structuring variable of springtails taxocenosis, and has lower annual amplitude temperatures. It registered abundance 10 times greater, and half the richness when compared to cave. There is indication that QF caves do not have conditions for formation of troglobites springtails, while the SSH maintains populations and conditions conducive to the evolutionary process of troglobites species. Therefore, adjustments are necessary in mechanisms used for Conservation and Environmental Monitoring in mining areas.